Variable Organizational Risk Preferences: Tests of the March-Shapira Model - Miller, Kent D.; Chen, Weiru (Academy of Management Journal, 2004)
March and Shapira's (1987, 1992) model of managers' risk preferences allows for shifts in attention between survival and aspiration levels. Our study provides initial empirical tests of their model using organizational data. We found that the variables affecting risk and the sizes (but not the signs) of these effects differed across performance categories. Organizations performing poorly showed increased risk as they neared bankruptcy. Other firms showed lower risk as performance improved relative to aspirations.